Establishing a molecular toolbox of lineage-specific real-time RT-PCR assays for the characterization of foot-and-mouth disease viruses circulating in Asia - Saduakassova, Meruyert A.; Wood, Britta A.; Henry, Elisabeth; Gray, Ashley R.; Mioulet, Valérie; Sultanov, Akhmetzhan A.; Wadsworth, Jemma; Knowles, Nick J.; Di Nardo, Antonello; King, Donald P.; Bachanek-Bankowska, Katarzyna (Frontiers in Veterinary Science, 2023)
Foot-and-mouth disease (FMD) is endemic in many Asian countries, with outbreaks occurring regularly due to viruses from serotypes O, A, and Asia1 that co-circulate in the region. The ability to rapidly characterize new virus occurrences provides critical information to understand the epidemiology and risks associated with field outbreaks, and helps in the selection of appropriate vaccines to control the disease. FMD lineage-specific characterization is usually determined through sequencing; however, this capacity is not always readily available. In this study, we provide a panel of real-time RT-PCR (rRT-PCR) assays to allow differentiation of the FMD virus (FMDV) lineages known to have been co-circulating in Asia during 2020. This panel included five new rRT-PCR assays designed to detect lineages O/ME-SA/PanAsia-PanAsia-2, O/ME-SA/Ind-2001, O/SEA/Mya-98, O/CATHAY, and A/ASIA/Sea-97, along with three published rRT-PCR assays for A/ASIA/Iran-05, A/ASIA/G-VII, and Asia1 serotypes. Samples of known FMD lineage (n = 85) were tested in parallel with all eight lineage-specific assays and an established 3D pan-FMD rRT-PCR assay, and comparative limit of detection (LOD) experiments were conducted for the five newly developed assays. All samples (85/85) were assigned to the correct serotype, and the correct lineage was assigned for 70 out of 85 samples where amplification only occurred with the homologous assay. For 13 out of 85 of the samples, there was amplification in two assays; however, the correct lineage could be designated based on the strongest Ct values for 12 out of 13 samples. An incorrect lineage was assigned for 3 out of 85 samples. The amplification efficiencies for the five new rRT-PCR assays ranged between 79.7 and 100.5%, with nucleic acid dilution experiments demonstrating broadly equivalent limits of detection when compared to the 3D pan-FMD rRT-PCR assay. These new tests, together with other published lineage-specific rRT-PCR assays, constitute a panel of assays (or molecular toolbox) that can be selected for use in FMD endemic countries (individually or a subset of the assays depending on region/lineages known to be circulating) for rapid characterization of the FMDV lineages circulating in Asia at a relatively low cost. This molecular toolbox will enhance the ability of national laboratories in endemic settings to accurately characterize circulating FMDV strains and facilitate prompt implementation of control strategies, and may be particularly useful in settings where it is difficult to access sequencing capability.